KURANG DATA, STATUS TAKSONOMI DAN HIBRID ALAMI DALAM KONSERVASI Rhododendron spp. DI INDONESIA - Rahman, Wiguna (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2008)
Red listing is a critical point in implementing conservation strategy of Indonesian Rhododendron spp. Some problems might be encountered during the process. Firstly, many of Indonesian Rhododendron species are on data deficient status, especially for non-Java species. Secondly, the existence of unstable species list that contains species names only known from few specimens. Thirdly, the legality of the conservation status for natural hybrids. Thus, promoting their natural habitat conservation and make them as monitoring remote areas for botanic gardens would be an important part of the conservation strategy.